Bedrunn3R: An intelligent running alarm clock - Ee, L.K. (Asian Research Publishing Network, 2015)
The conventional alarm clocks have been serving their purpose to mankind since their inception, to wake people up every single morning. However, the rates of oversleeping are still on the rise and people are having trouble waking up in the morning even with the use of alarm clocks. The snooze button that is available on all conventional alarm clocks provide user with more sleep but at a cost of deteriorating their quality of health and exacerbating sleep inertia at the same time. The objective of this paper is to study the problems associated with sleep that are often faced by people and to develop an intelligent moving alarm clock that implements the application of Artificial Intelligence. The Hypothetico-Deductive method will be used as the research methodology while the development will be following the Rapid Application Development (RAD) model. The developed prototype is tested against conventional alarm clocks and has shown significant improvements in the percentages of oversleeping and snoozing. Recommendations for continuation and future work of this paper are also included.